7
$\begingroup$

Prove that there are no integers $x, y, z$ such that $x+y+z=0$ and $\frac1x+\frac1y+\frac1z=0$

My thinking was that since the numbers are integers, then there can't be $2$ negative values that cancel out the positive or $2$ positive numbers to cancel the negative. One integer would have to cancel out the second, and the third wouldn't make the sum zero. Am I right?

$\endgroup$
  • $\begingroup$ The statement remains to be true even when $x,y,z$ are allowed to be non-zero real numbers. $\endgroup$ – achille hui Jan 27 '18 at 3:44
4
$\begingroup$

We can assume that $gcd(x,y,z)=1$;

$(1/x+1/y+1/z)xyz=xy+xz+yz=x(y+z)+yz$, $x+y+z=0$ implies that $y+z=-x$, we have $x(y+z)+yz=-x^2+yz=0$. We deduce that $x^2=yz$, let $p$ be a prime which divides $x$, $p$ divides $yz$ implies that $p$ divides $y$ or $z$, suppose that $p$ divides $y$, $-x/p=-y/p+z/p$ implies $p$ divides $z$, contradiction. We deduce that $x=1$ or $x=-1$, the same argument shows that $y,z\in\{-1,1\}$. This is impossible.

$\endgroup$
  • $\begingroup$ Why can we assume that their greatest common divisor is $1$? $\endgroup$ – Joe Johnson 126 Jan 27 '18 at 4:13
  • 1
    $\begingroup$ because you can divide $x,y,z$ by a common divisor and obtain $x',y',z'$ which is also a solution. $\endgroup$ – Tsemo Aristide Jan 27 '18 at 4:45
8
$\begingroup$

The statement remains to be true even when one allow $x, y, z$ to be real numbers.

In order for the second condition $\frac{1}{x} + \frac{1}{y} + \frac{1}{z} = 0$ to make sense, none of $x, y, z$ can be zero.
If the first condition $x + y + z = 0$ is also satisfied, we will have

$$x^2 + y^2 + z^2 = (x+y+z)^2 - 2\left(\frac1x + \frac1y + \frac1z\right)xyz = 0^2 - 0 = 0$$ As long as $x,y,z$ are real numbers, this forces $x = y = z = 0$ and makes second condition absurd.

$\endgroup$
  • $\begingroup$ What's property this proof uses called? $\endgroup$ – Sudix Jan 27 '18 at 6:05
  • 2
    $\begingroup$ @Sudix the technical term is real numbers form an ordered integral domain. For practical purposes, what we need to know is if $x \ne 0$, then $x^2$ is positive. Since the sum of positive number and non-negative numbers is positive, if $x^2+y^2+z^2$ is $0$, none of $x^2$, $y^2$ and $z^2$ can be positive. This forces $x = y = z = 0$. $\endgroup$ – achille hui Jan 27 '18 at 9:48
4
$\begingroup$

Another proof using symmetric polynomials/Vieta's formulas. This generalizes to any field.

Let $\sigma_1=x+y+z$, $\sigma_2=xy+yz+xz$, and $\sigma_3=xyz$ be the elementary symmetric polynomials. In order to make sense of $\frac{1}{x}+\frac{1}{y}+\frac{1}{z}=0$, we can assume that $xyz\ne 0$. Then $\sigma_3(\frac{1}{x}+\frac{1}{y}+\frac{1}{z})=\sigma_2$, so $\sigma_2=0$. Thus we know $\sigma_2=\sigma_3=0$. Now by Vieta's formulas, $x$, $y$, and $z$ are the roots of the cubic polynomial $t^3-\sigma_1t^2+\sigma_2t-\sigma_3=t^3-xyz$. Hence $x^3-xyz=0$, and similarly for $y$ and $z$, so we get $$x^3=y^3=z^3=xyz.$$ Dividing this equation by $x^3$, we get $$\newcommand{\of}[1]{\left({#1}\right)}1=\of{\frac{y}{x}}^3=\of{\frac{z}{x}}^3=\frac{y}{x}\frac{z}{x}.$$

Now there are two cases. The first case is that $y/x=z/x=1$, in which case $x=y=z$. Together with $x\ne 0$ and $x+y+z=3x=0$, we see that $3=0$, so this case can only happen if the characteristic of the field is 3. In that case, $x=y=z=c$ for any nonzero constant $c$ gives a solution. In particular this can't happen for $\Bbb{Q}$, so there are no integral solutions to the equation in this case.

The other case is that $y/x=\omega$ where $\omega\ne 1$, but $\omega^3=1$. This can only happen when the characteristic of $K$ is not three, since in characteristic three $(t^3-1)=(t-1)^3$, so in characteristic three, the only cube root of unity is 1. (Note that $\omega^3=1$ and $\omega\ne 1$, together imply that $\omega$ satisfies the polynomial $1+t+t^2$.) Then for any nonzero constant $c$, $x=c$, $y=\omega c$, $z=\omega^2 c$ gives a valid solution and these are the only solutions, since $x+y+z=c+\omega c+\omega^2 c= c(1+\omega+\omega^2)=0$, and $\frac{1}{x}+\frac{1}{y}+\frac{1}{z} = \frac{1}{c}+\frac{1}{c\omega}+\frac{1}{c\omega^2}=\frac{1}{c}\of{1+\omega^2+\omega}=0$. However, once again, there are no primitive cube roots of one in $\Bbb{Q}$, so this case cannot yield any integral solutions.

Note however that there are solutions over $\Bbb{C}$ (namely $1,\omega,\omega^2$, where $\omega=e^{2\pi i/3}$).

To summarize, we have a complete description of solutions to these equations for any field $K$.

The form of the solutions depends on the characteristic of $K$. If the characteristic is 3, the solutions are of the form $x=y=z=c\ne 0$ for any nonzero constant $c$. Otherwise, there are solutions in $K$ if and only if the equation $1+t+t^2$ has a solution $\omega$ in $K$, in which case the solutions are precisely of the form $x=c$, $y=c\omega$, $z=c\omega^2$ for any nonzero constant $c$.

$\endgroup$
  • $\begingroup$ This was my first reaction to seeing the question. Thanks for saving me the trouble of writing. $\endgroup$ – Jyrki Lahtonen Jan 27 '18 at 10:26
2
$\begingroup$

Assume there are. W.l.o.g. $y$ and $z$ are positive. Then $$x=-y-z \implies 0 = \frac{-1}{y+z} +\frac{1}{y}+\frac{1}{z} = \frac{-yz+z(y+z) +y(y+z)}{yz(y+z)} = \frac{z^2+y^2+yz}{yz(y+z)} >0,$$ contradiction. Note that this works for $x,y,z\in \Bbb R$.

$\endgroup$
2
$\begingroup$

Let $x,y,z \not = 0$ be integers.

$1$) Multiply $\dfrac1x+\dfrac1y+\dfrac1z=0$ by $xyz:$

$$zy + zx + yx=0.$$

$2$) Square $x+y +z = 0:$

$$x^2+y^2+z^2 + 2(xy +xz +yz) =0$$

Second term is $0$, see $1$).

Hence : $$x^2+y^2+z^2= 0.$$

A contradiction, we assumed $x,y,z \not = 0$ are integers.

$\endgroup$
  • $\begingroup$ Simplifire.Thanks for your kind words. $\endgroup$ – Peter Szilas Jan 27 '18 at 16:41
  • 1
    $\begingroup$ It seems to me that you haven't actually used the assumption that $x,y,z$ are integers, so in fact you have proved the result for arbitrary real numbers (which is an improvement over the original problem--proving the same result with fewer hypotheses). $\endgroup$ – awkward Jan 27 '18 at 21:11
1
$\begingroup$

We can't have any of $x,y$ or $z$ equal to zero, because we need their reciprocals, so there must be either two positives and a negative, or one positive and two negatives. Since you can multiply both sides by $-1$, these are actually the same case. Then you can just think about how, when $2+3-5=0$, we don't have $\frac12+\frac13-\frac15=0$, and even though $\frac1{30}+\frac1{15}-\frac1{10}=0$, we don't have $30+15-10=0$

$\endgroup$
0
$\begingroup$

We have that $$x+y=-z\quad\text{ and }\quad\frac1x+\frac1y=-\frac1z\\\implies\frac1{x+y}=\frac1x+\frac1y\implies (x+y)^2=xy\\\implies x^2+y^2=-xy\implies-\frac{x}y-\frac{y}x=1\tag1$$ for some $x,y,z\in\Bbb Z\setminus\{0\}$. Setting $r:=-\frac{x}y$ the last identity result in

$$r+r^{-1}=1\tag2$$

for some $r\in\Bbb Q\setminus\{0\}$, what is not possible because

$$r+r^{-1}=\frac{r^2+1}r=1\implies r^2-r+1=0\tag3$$

what doesnt have real solutions.

$\endgroup$
0
$\begingroup$

Alternatively, denote: $y=ax,z=abx$, then: $$\begin{cases}x+ax+abx=0 \\ \frac{1}{x}+\frac{1}{ax}+\frac{1}{abx}=0\end{cases} \Rightarrow \begin{cases}1+a+ab=0 \\ 1+\frac{1}{a}+\frac{1}{ab}=0\end{cases} \Rightarrow \begin{cases}a=-\frac{1}{b+1} \\ b^2+b+1=0\end{cases} \Rightarrow \emptyset.$$

$\endgroup$
0
$\begingroup$

Hint: if $x+y+z=0$, then $$ \begin{align} \frac1x+\frac1y+\frac1z &=\frac1x+\frac1y-\frac1{x+y}\\ &=\frac{(x+y)^2+x^2+y^2}{2xy(x+y)}\\ &=-\frac{x^2+y^2+z^2}{2xyz} \end{align} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.